Correlation of executive functions, academic achievement, eating behavior and eating habits in university students of Mexico City - Chavez-Hernandez, Maria Elena (Frontiers in Education, 2023)
Young adults between 18 to 25 years of age are in an important transitional time and university students are considered vulnerable given that they generally maintain an unhealthy lifestyle characterized by poor diet quality and meal skipping. Therefore, the aim of the present study was to evaluate the relationship between executive functions, academic achievement, eating behavior, eating habits, and BMI in university students. 1903 university students (1038 women, 865 men), with a mean age of 20.65 years (SD ±1.66), participated in the study. Spearman's r correlation analysis revealed that there is a significant correlation between all variables of interest, with the most significant correlations found with academic achievement, emotional eating, and eating habits. Our study confirms previous findings in the association between EF, eating habits, eating behavior, and academic achievement in university students, and also provides a first approach to the association between UP food intake, overall meal skipping (breakfast, lunch, and/or dinner) and EF.